2018
DOI: 10.1186/s12891-018-2138-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of flat surface design and medial pivot design in posterior cruciate-retaining total knee arthroplasty: a matched pair cohort study of two years

Abstract: BackgroundComponent design is one of the contributory factors affecting the postoperative flexion angle. The purpose of this study was to compare short-term outcomes of flat surface and medial pivot designs in posterior cruciate-retaining (CR) total knee arthroplasty (TKA).MethodsA retrospective, case-control, and observational cohort study consisted of matched-pairs of the flat surface design (Hi-Tech Knee II) and the medial pivot design (FINE Knee) in CR-TKA with a two-year follow-up period.ResultsHi-Tech Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Uvehammer et al demonstrated that the Hospital for Special Surgery knee score and the patients' opinion based on their preoperative expectations were not very different [20]. On the other hand, a two-year matched pair cohort study demonstrated that the clinical outcomes of the medial pivot design used in CR-TKA were more favorable than those of the at surface design [21]. It is di cult to draw conclusions about which is better, but the absence of signi cant differences in clinical scores shown by Uvehammer et al suggests that even the at surface allows medial pivot motion when appropriate ligament balances are achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uvehammer et al demonstrated that the Hospital for Special Surgery knee score and the patients' opinion based on their preoperative expectations were not very different [20]. On the other hand, a two-year matched pair cohort study demonstrated that the clinical outcomes of the medial pivot design used in CR-TKA were more favorable than those of the at surface design [21]. It is di cult to draw conclusions about which is better, but the absence of signi cant differences in clinical scores shown by Uvehammer et al suggests that even the at surface allows medial pivot motion when appropriate ligament balances are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Those are concerns in TKA with the medial pivot design. Clinical studies comparing at vs. concave inserts have been made and reported [20,21]. Uvehammer et al demonstrated that the Hospital for Special Surgery knee score and the patients' opinion based on their preoperative expectations were not very different [20].…”
Section: Discussionmentioning
confidence: 99%
“…As far as MP total knee arthroplasty is concerned, there are limited studies comparing its outcomes with those of other implant designs (Table 3). 5,13,[18][19][20][21][22][23][24][25] To date, there is only one randomized study by Hossain et al, 5) which has compared outcomes of an MP knee to a fixed-bearing multi-radius PS implant. There are three other randomized controlled trials (RCTs), which have compared an MP design to a mobile PS knee: an ultra-congruent rotating platform knee in studies by Kim et al 18) and Kim et al 19) and a single radius knee in a study by Benjamin et al 20) There are a few more matched pair studies and case series, which have looked at outcomes of the MP design.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies [19,23,27,35,39,41,43,48] Minor (< 2 mm) and non-progressive femoral radiolucent lines were found in 146 (7.5%) knees on the femoral side and in 175 (9.0%) cases on the tibial side. Major or progressive femoral RLL were reported in 11 (0.5%) cases.…”
Section: Radiographic Outcomesmentioning
confidence: 99%